Penerapan Metode Extreme Programming dalam Pengembangan Sistem Pemantauan Konstruksi Kapal Berbasis Web - Fadlin Azhary (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Construction management is vital for coordinating and overseeing projects to ensure alignment with planned objectives. Factors such as time, cost, and quality demand strict control, as discrepancies between initial plans and actual execution can cause significant challenges. In ship construction, delays in material execution and delivery are frequent bottlenecks, leading to schedule disruptions and negatively affecting project outcomes. Addressing these issues requires effective management and robust risk mitigation strategies. This study proposes a web-based ship construction project monitoring system using the Laravel framework and MySQL database. The system is developed using Extreme Programming (XP), an agile methodology that emphasizes iterative improvement, stakeholder collaboration, and adaptability. XP practices, including test-driven development, pair programming, and continuous integration, ensure the system is reliable, adaptive, and responsive to evolving user needs. Frequent stakeholder feedback and incremental development cycles enable the system to tackle dynamic challenges, optimize resource utilization, and ensure timely project delivery. By incorporating XP principles, this study demonstrates the potential of agile methodologies to enhance construction project management. The resulting system provides a flexible and efficient solution for mitigating delays and improving the overall success of ship construction projects.